PENGARUH PEMBERIAN KOMPOS DARI TANDAN KOSONG KELAPA SAWIT TERHADAP PERTUMBUHAN SAWI CAISIM (BRASSICA JUNCEA L.) - Villani, Romilda; Suwondo; Imam Mahadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The use of organic fertilizers is one approach to enhance plant growth while simultaneously utilizing agricultural waste available in the surrounding environment. Empty fruit bunches of oil palm (EFBOP) are solid residues from palm oil processing that have the potential to be used as compost due to their nutrient content, including N, P, K, Mg, and Ca. This study aimed to determine the effect of compost derived from empty fruit bunches of oil palm on the growth of caisim (Brassica juncea L.), particularly in terms of plant height, number of leaves, leaf width, and fresh weight. The study employed an experimental method using a factorial Randomized Block Design (RBD) consisting of seven treatments with three replications. Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that the application of compost had a significant effect on the growth of caisim. The drum compost treatment at a concentration of 3 kg/plot produced the highest plant height, leaf width, and fresh weight, while the EFBOP compost at a concentration of 1 kg/plot resulted in the highest number of leaves. These findings indicate that compost from empty fruit bunches of oil palm is effective as an organic fertilizer to support the growth of caisim.